1983
DOI: 10.1159/000280887
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma Causing Spontaneous Rupture of the Kidney

Abstract: A case of spontaneous rupture of a renal angiomyolipoma with massive retroperitoneal haemorrhage necessitating emergency nephrectomy is presented. Diagnostic features and treatment of angiomyolipoma are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

1985
1985
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
6
0
2
Order By: Relevance
“…There have been fre quent reports of symptomatic renal angiomyolipoma with flank pain as a sign of spontaneous bleeding into the tumor [7,8,11,13,15], There are only few reports of massive retroperitoneal bleeding from the tumor causing unclear abdominal symptoms and even acute abdominal symptoms [17]. There has been no report of acute abdominal symptoms combined with obstipation, caused by the mass of the tumor, as in our case.…”
Section: Discussionmentioning
confidence: 50%
“…There have been fre quent reports of symptomatic renal angiomyolipoma with flank pain as a sign of spontaneous bleeding into the tumor [7,8,11,13,15], There are only few reports of massive retroperitoneal bleeding from the tumor causing unclear abdominal symptoms and even acute abdominal symptoms [17]. There has been no report of acute abdominal symptoms combined with obstipation, caused by the mass of the tumor, as in our case.…”
Section: Discussionmentioning
confidence: 50%
“…According to Kristofferson et al [26], 10 cases had been reported up to 1986 [25,27], In our patient the hemor rhage, which could not be controlled by conservative means, was a compelling indication for nephrectomy. On the other hand, the goal in the treatment of symptomatic angiomyolipomas must be to retain as much as possible of the functional kidney tissue.…”
Section: Recurrent Bleeding O F Angiomyolipomas In Tuberous Sclerosismentioning
confidence: 57%
“…There are relatively few reports [25,27] of massive ret roperitoneal hemorrhage from the tumor, leading to un clear abdominal symptoms or in some cases an acute abdominal complaint leading to immediate surgery [25]. According to Kristofferson et al [26], 10 cases had been reported up to 1986 [25,27], In our patient the hemor rhage, which could not be controlled by conservative means, was a compelling indication for nephrectomy.…”
Section: Recurrent Bleeding O F Angiomyolipomas In Tuberous Sclerosismentioning
confidence: 69%
“…Besides adenocarcinomas, renal tumors that have been reported to bleed spontaneously include papillary carcinoma of the renal pel vis [3], angiomyolipoma [1,[4][5][6][7], angiosarcoma [8], adenoma [9], fibromyoma [10], fibroxanthoma [11] and Wilms' tumors [1], This case refers to a renal cell sarcomatous carcinoma co-expressing both cytokeratin and vimentin and presenting as spontaneous retroperi toneal hemorrhage.…”
Section: Introductionmentioning
confidence: 99%